The levels of fulfilment the duties of school family association board of directors in primary schools - Goekyer, Necmi (Elsevier Science Bv, 2010)
The purpose of this study is to determine the levels of fulfilment the duties of school parent association (SPA) directors board. The sample of the study by using a descriptive model was comprised of 20 schools which formed SPA and were chosen from four central districts in Diyarbakir Metropolitan Municipality by random sampling method in the 2009-2010 academic year. Each schooI's principal, a vice principal, a teacher who was chosen among the teachers and four members who were selected among the parents serve in SPA Board of Directors. 20 school principals, 20 vice principals, 20 teachers and 80 parents were sampled. Groups'opinion were obtained with 25 survey questions which were generated from the sixth item of the SPA Regulation. According to the averages, t test, analysis of variation and Scheffe test findings, principals, teachers and parents reports that they perform their duties at the level of 'rare' and 'occasionally' in terms of duty, gender and educational level variables. It was concluded that the groups did not fulfill the task-oriented activities largely.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: School-Parent Association; The Duties of School-Parent Association Board of Directors; School-Parent Association Board of Directors; Primary School